Improving Family Economy through the Quality Family Village Program (Kampung KB) in Sumurbatu Village, Cikeusik District, Pandeglang Regency, Banten Province - Nana Nofianti (EQUATOR SINAR AKADEMIA, 2023)
Quality Family Village (Kampung KB) is defined as a regional unit at the village level where there is integration and convergence in the implementation of empowerment and strengthening of family institutions in all its dimensions in order to improve the quality of human resources, families and communities. As a development approach that is universal, and in order to improve quality of human resources as well as optimizing the implementation of empowerment to strengthen family institutions, it is necessary to encourage the implementation of Quality Family Villages in every village/kelurahan. For this reason, the KKM 16 Thematic UNTIRTA group carried out and socialized the Quality Family Village Work Program (Kampung KB) to improve the quality of life of the people in Sumurbatu Village, Cikeusik District, Pandeglang Regency, Banten Province. The implementation of this socialization uses the seminar method where the teaching materials are presented by the speaker to the residents. The results obtained were community enthusiasm in implementing the Quality Family Village Program (KB Village) in Sumurbatu Village